2005
DOI: 10.1002/chem.200400746
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Influence of the Structure of the Glycosyl Acceptors on the Stereochemistry of the Glycosylation Reactions with 2‐Azido‐2‐Deoxy‐Hexopyranosyl Trichloroacetimidates

Abstract: The stereochemical outcome of glycosylations with 2-azido-2-deoxy-D-gluco- and D-galactopyranosyl trichloroacetimidates as glycosyl donors has been investigated by using a series of chiro-inositol derivatives as glycosyl acceptors. The influence of the absolute configuration, the conformation and the conformational flexibility of the glycosyl acceptor has been studied by using different glycosyl donors under similar pre-established experimental conditions. Although the structure of the acceptor may play a role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…Probing of the existence of diastereomeric matching and mismatching, through the use of an enantiomeric pair of acceptors with an enantiomerically pure donor or the converse [93], might be considered as another possible entry into determining the extent of involvement of the acceptor in a glycosylation reaction. For example, a pair of coupling reactions exhibiting a high degree of diastereomeric discrimination as in the coupling of perbenzoyl Dand L-fucosyl bromides (D-3 and L-3) with the Dglucosamine based acceptor D-4 resulting in two sets of two anomers (Scheme 8) [93] must be considered as having a relatively tight transition state, whereas one with little or no such discrimination, as in the coupling of the enantiomeric chiro-inositol acceptors D-and L-6 with the D-2-azido-2-deoxy glucopyranosyl trichloroacetimidate donor D-7 (Scheme 9) [94], necessarily is highly exploded.…”
Section: The Role Of the Acceptor In The Glycosylation Mechanismmentioning
confidence: 99%
“…Probing of the existence of diastereomeric matching and mismatching, through the use of an enantiomeric pair of acceptors with an enantiomerically pure donor or the converse [93], might be considered as another possible entry into determining the extent of involvement of the acceptor in a glycosylation reaction. For example, a pair of coupling reactions exhibiting a high degree of diastereomeric discrimination as in the coupling of perbenzoyl Dand L-fucosyl bromides (D-3 and L-3) with the Dglucosamine based acceptor D-4 resulting in two sets of two anomers (Scheme 8) [93] must be considered as having a relatively tight transition state, whereas one with little or no such discrimination, as in the coupling of the enantiomeric chiro-inositol acceptors D-and L-6 with the D-2-azido-2-deoxy glucopyranosyl trichloroacetimidate donor D-7 (Scheme 9) [94], necessarily is highly exploded.…”
Section: The Role Of the Acceptor In The Glycosylation Mechanismmentioning
confidence: 99%
“…The extrapolation of the stereoselectivity of benzylidene glucose donors to their glucosazide counterparts suggests that benzylidene or analogously protected glucosazides might represent an attractive class of 1,2- cis -selective glucosamine donor synthons. 20,21 …”
Section: Introductionmentioning
confidence: 99%
“…The in-depth research conducted on conformationally restricted benzylidene mannose and glucose donors has provided important insight into the glycosylation mechanisms of this type of 1,2- cis -selective donor. To construct 1,2- cis linkages of glucosamine donors, the C-2-amino group is most commonly masked as the nonparticpating azide. , Notably, benzylidene glucosazides have not been systematically investigated with respect to the stereoselectivity of glycosylations in which they are employed. The extrapolation of the stereoselectivity of benzylidene glucose donors to their glucosazide counterparts suggests that benzylidene or analogously protected glucosazides might represent an attractive class of 1,2- cis -selective glucosamine donor synthons. , …”
Section: Introductionmentioning
confidence: 99%
“…5.34) with different glycosyl donors, in particular 2-azido-2-deoxy-glycopyranosyl trichloroacetimidates. In an attempt to extend the applicability of the double stereodifferentiation principle [59] to glycosylation reactions [60], Martin-Lomas et al studied the stereoselectivity of the glycosylation of D-and L-chiro-inositol derivatives with several glycosyl donors [61]. The authors observed that when differently protected 1,2-diols, derived from both chiroinositol enantiomers, are used as acceptors, both the absolute configuration of the acceptor as well as the nature of the donor's and acceptor's protecting groups plays a key role in the regiochemistry of the coupling.…”
Section: Regio-and Stereoselectivity In Glycosylationmentioning
confidence: 99%